Actoprotective activity of 5-(2-bromophenyl)-4-amino-4H-1,2,4-triazole-3-thione and its S-derivatives - Ye. S. Pruglo (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. The paper shows the actoprotective (anti-fatigue), activity of 1,2,4-triazole derivatives.